Kontribusi Penerapan Strategi Marketing Mix Islam Dalam Peningkatan Kinerja : Studi Pada Baitul Mal Wattamwil (BMT) Usaha Gabungan Terpadu (UGT) Sidogiri Di Kabupaten Situbondo - Akrim Billah; Malikul Irfan (LP3M INSTITUT KH YAZID KARIMULLAH, 2022)
The 4.0 Industrial Revolution is currently a hot topic of discussion by economic practitioners, academics and entrepreneurs. Because it requires that the elements have competitiveness from various aspects, so they can realize what they aspire to. Especially those engaged in Sharia business. Along with the development of the Sharia Business world, also developed macro and micro economies that are oriented to Islamic Sharia, and also developed Islamic Financial Institutions, Islamic financial institutions consisting of banks (consisting of Islamic commercial banks and Islamic credit banks), and institutions non-bank financial institutions, one of which is micro, namely Baitul Maal wa Tamwil (Sudarsono, 2009: 8). Baitul Maal wat-Tamwil (BMT) operates based on sharia principles which have a function to empower the economy of the people, and have a social function. Nowadays, with the rapid growth of BMT, people are starting to look to invest funds and use BMT services. In order to be able to compete in this Disruption era, the BMT UGT Sidogiri Situbondo Branch requires that the concentration of its development be on 7 important points; namely product, price, place, promotion, process, people, and physical evidence. in order to be able to survive the value of trust (Trust) to the Community. By combining according to Islamic Marketing Principles The principle of Islamic marketing combines the concept of maximizing value with the principle of 'justice' for the welfare of the wider community. These principles offer the means to create value and improve the standard of living of the community at large through commercial activities. Islamic ethical guidelines guarantee the respect and freedom of individuals, both bankers and customers.